Prediction of soil organic carbon loss due to erosion in Girindulu Watersheds - D Mey; J Sartohadi; D Mardiatno; M A Marfai (Brawijaya University, 2015)
This research aimed to predict soil loss and soil organic carbon loss due to the erosion in the Girindulu watershed. The population of the research was all landforms in the Girindulu watershed. The research sample was representative in representing landform unit characteristic of the population. Data collection was conducted through soil surveys and laboratory analysis, and the sampling technique was purposive sampling. The collected data were the characteristics of the land, climate, and soil erosion and related carbon organic. The amount of soil organic carbon loss was predicted using the equation of COT= 2.1091(totSed)0.025, and the total sediment transported by erosion was predicted using the equation of totSed = 0.6808+ 0,854Ch+0.435BO–2.125pL+1.98mL. The results showed that the Girindulu watershed area of 73,703.75 ha had a total soil loss due to erosion of 9,880,934.7 t/year, and total soil organic carbon loss due to erosion of 153,120.2 t/year. Soil and soil organic carbon loss affected pool of C stock on landform, climate condition (rainfall), geomorphologycal condition (the presence of a geological fault, length slope and land slope), soil characteristics (texture and organic matter), and human activity in agricultural society management. Soil conservation actions need to be taken through replanting of trees (reforestation) in marginal lands, incorporation of agricultural residues, mulching with organic matter from vegetation, and application of organic fertilizer on cultivated land.